Characterization of Chickpea Genotypes (Cicer arietinum L.) Through Chemical Tests - LK SHARMA; GU KULKARNI; JB PATEL (Seed Research, 2026)
An experiment was carried out to characterize twenty-five chickpea genotypes based on rapid chemical tests and seed quality parameters. Seeds were subjected to NaOH, CuSO4, Na2CO3, KOH, FeSO4 reactions and GA3 growth response test for differentiating the genotypes. Based on the NaOH test, the genotypes were grouped into dark yellow (7 genotypes), light yellow (8 genotypes) and no colour reaction (10 genotypes). CuSO4 and Na2CO3 test, could not differentiated the genotypes. Based on the KOH test, the genotypes were grouped into black (16 genotypes), dark brown (8 genotypes) and no change (1 genotype). Based on the FeSO4 test, the genotypes were grouped into black (24 genotypes) and no change (1 genotype). Among 25 genotypes, gowth response test with GA3 was high in all.